Al‐Modified Zinc Oxide Nanorods for Photoelectrochemical Water Oxidation. Issue 4 (7th October 2013) - Fekete, Monika; Ludwig, Wiebke; Gledhill, Sophie; Chen, Jie; Patti, Antonio; Spiccia, Leone
Abstract: The photoassisted water oxidation by a range of electrodeposited Al‐modified zinc oxide nanorod arrays (NRAs) has been explored in a standardised photoelectrochemical cell. The nanorods were prepared by electrodeposition onto fluorine‐doped tin oxide glass substrates from warm aqueous solutions of zinc nitrate and aluminium nitrate. Photoluminescence measurements suggested that the nanorods have a very low concentration of defects that could act as centres for undesired charge recombination. The effect of NRA aluminium modification, morphology and optical properties as well as the presence of sputtered i‐ZnO and aluminium‐doped ZnO seeding layers on the catalytic performance of the films were investigated. Water oxidation was observed under 1 Sun illumination even at very low applied potentials (0 V vs. Ag/AgCl at pH 9.2). The pure ZnO nanorods yielded a relatively high photocurrent of 0.52 mA cm –2 (at 1 V vs. Ag/AgCl). Al modification of the sputtered seeding layer and/or the NRAs did not change the performance significantly. The photocurrent was further increased by exchanging the sputtered ZnO seeding layer for a galvanostatically deposited seeding layer. In this case the photocurrent increased to 0.74 mA cm –2 (at 1 V bias). Light absorbance and IPCE measurements indicated that although all NRAs absorb well in the UV region, light conversion does not extend greatly into the visible region. To address the issue of rapid photodegradation during water oxidation catalysis, the effect of electrolyte pH was explored by using phosphate and borate buffers with a view to improving photocurrent and long‐term stability. A borate buffer at pH 9.2 was found to be the most suitable. In this case, the photocurrent of undoped ZnO and aluminium‐doped ZnO NRA films was sustained at a high level on continuous illumination with a reduction of less than 10 and 30 %, respectively, over 1 hour, as opposed to almost complete deactivation after 20 min as observed in 0.1M Na2 SO4 (pH 6). These results indicate that the ZnO NRAs presented here have the potential to become viable photoelectrocatalysts for water oxidation. Abstract : Pristine and aluminium‐modified zinc oxide nanorod arrays, prepared by low‐temperature electrodeposition, have been tested as water oxidation photoanodes under 1 Sun illumination and exhibited high photocurrents even at low applied potentials. Long‐term stability was improved by using phosphate and borate buffers.